Site-Directed Fluorescence Approaches for Dynamic Structural Biology of Membrane Peptides and Proteins - Raghuraman, H.; Chatterjee, Satyaki; Das, Anindita (Frontiers in Molecular Biosciences, 2019)
Membrane proteins mediate a number of cellular functions and are associated with several diseases and also play a crucial role in pathogenicity. Due to their importance in cellular structure and function, they are important drug targets for 60% of drugs available in the market. Despite the technological advancement and recent successful outcomes in determining the high-resolution structural snapshot of membrane proteins, the mechanistic details underlining the complex functionalities of membrane proteins is least understood. This is largely due to lack of structural dynamics information pertaining to different functional states of membrane proteins in a membrane environment. Fluorescence spectroscopy is a widely used technique in the analysis of functionally-relevant structure and dynamics of membrane protein. This review is focused on various site-directed fluorescence (SDFL) approaches and their applications to explore structural information, conformational changes, hydration dynamics, and lipid-protein interactions of important classes of membrane proteins that include the pore-forming peptides/proteins, ion channels/transporters and G-protein coupled receptors.